2019
DOI: 10.2516/ogst/2019062
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic optimization of methanol synthesis section in the dual type configuration to increase methanol production

Abstract: The main object of this research is dynamic modeling and optimization of the methanol synthesis section in the dual type configuration considering catalyst deactivation to improve methanol production capacity. In the methanol unit, deactivation of CuO/ZnO/Al 2 O 3 catalyst by sintering and low equilibrium conversion of reactions limit the production capacity, and changing operating temperature is a practical solution to overcome the production decay. In the first step, the considered process is modeled based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, on an industrial scale, it is common practice to feed methanol reactors with syngas close to the stoichiometric condition (optimal SN is 2.05 as investigated by Løvik and co-workers) and excess of H 2 (2 < H 2 /CO < 3) with a variable amount of CO 2 (i.e., variable COR) according to the installed syngas generation technology. This means that the most common case in an industrial plant is represented by bio-syngas and petro-syngas feedstocks as reported in the literature case studies ,, and real methanol industrial plants’ data. , However, CO 2 /H 2 mixtures as feedstocks for methanol synthesis are under investigation, and they are becoming more and more appealing for their sustainability and environmental reasons , although carbon capture utilization and sequestration (CCUS) still represents a relevant cost factor in industrial plants as recently reported by the IEA…”
Section: Resultsmentioning
confidence: 99%
“…However, on an industrial scale, it is common practice to feed methanol reactors with syngas close to the stoichiometric condition (optimal SN is 2.05 as investigated by Løvik and co-workers) and excess of H 2 (2 < H 2 /CO < 3) with a variable amount of CO 2 (i.e., variable COR) according to the installed syngas generation technology. This means that the most common case in an industrial plant is represented by bio-syngas and petro-syngas feedstocks as reported in the literature case studies ,, and real methanol industrial plants’ data. , However, CO 2 /H 2 mixtures as feedstocks for methanol synthesis are under investigation, and they are becoming more and more appealing for their sustainability and environmental reasons , although carbon capture utilization and sequestration (CCUS) still represents a relevant cost factor in industrial plants as recently reported by the IEA…”
Section: Resultsmentioning
confidence: 99%
“…55 Accordingly, the deactivation model derived by Honken, 56 shown in eqn (12), was found to be suitable for representing the catalyst deactivation in many industrial scale applications. [57][58][59][60][61][62][63] Rahimpour et al 64 applied a seventh-order catalyst deactivation model to study the dynamic catalyst deactivation from carbonic coke formation during naphtha reforming reactions at 502-504 °C and pressure 34-37 bar, in which carried out in a radial ow spherical reactor as shown in eqn (13).…”
Section: Temperature Dependent Catalyst Deactivation Modelmentioning
confidence: 99%
“…Masoudi et al succeeded in increasing the methanol production capacity by 6.45% over a conventional dual-type reactor through the dynamic modeling of a dual-type methanol synthesis section. They considered catalyst deactivation and optimization of the feed temperature, cooling water temperature, and other factors to manage the heat . Pérez-Fortes et al developed a technology for converting CO 2 to DME through the three-stage reformation of methane, a low-cost feedstock, with a DME synthesis unit …”
Section: Introductionmentioning
confidence: 99%
“…To optimize the design variables efficiently, we use machine learning. Askari et al and Masoudi et al applied a genetic algorithm to a methanol synthesis section and improved the methanol production capacity. , Omata et al combined a genetic algorithm with a neural network to optimize the temperature profile of a temperature gradient reactor, thus improving the conversion of CO under low-pressure conditions . Previous studies have optimized the design variables for certain subprocesses, but the entire process has not been considered in the optimization.…”
Section: Introductionmentioning
confidence: 99%